A World Beyond Transnational Corporations: Meeting Human Rather Than Corporate Need; Comment on "'Part of the Solution': Food Corporation Strategies for Regulatory Capture and Legitimacy" - Fran Baum; Julia Anaf (Kerman University of Medical Sciences, 2022)
This paper provides a commentary on Lacy-Nichols and Williams' analysis of the emerging tactics of the ultraprocessed food transnational corporations (TNCs). Our paper provides an overview of the growth in power and influence of TNCs in the past three decades and considers how this change impacts on health and health equity. We examine how wealth inequities have increased dramatically and how many of the health harms are externalised to governments or individuals. We argue that human interests and corporate interests differ. The article concludes with a consideration of alternative ways of organising an economy that are more human centred and health promoting. We suggest five changes are required: improved measurement of economic outputs beyond gross domestic product (GDP); improved regulation of finance and TNCs; development of localised economic models including cooperatives; reversal of privatisations; making the reduction of economic inequalities a goal of financial policy. We consider the barriers to these changes happening.